STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN GURU DI SDN NO. 2 PANCOR - Rohiqi Karima Jati; Muh. Sya’roni; Ahmad Subyanto (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Teacher discipline is a fundamental factor in improving the quality of education, as it is directly related to professional responsibility and the effectiveness of learning. In this context, the principal plays a strategic role as a leader, mentor, and key motivator in fostering a culture of discipline within the school environment. This study aims to identify the principal's strategies in enhancing teacher discipline and the factors that influence it at SDN 2 Pancor. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The validity of the findings was ensured through source triangulation techniques. The results of the study indicate that the principal implements various strategies to promote teacher discipline, including the establishment of duty schedules, role modeling in attendance and behavior, implementation of a reward and punishment system, regular evaluations, the requirement for teachers to prepare lesson plans, and collaboration with the school community, committee, and parents. Factors influencing the success of these strategies include teacher compliance with working hours, consistency of attendance, and preparedness of teaching materials. Therefore, the strategies implemented by the principal at SDN 2 Pancor have proven effective in improving teacher discipline. These strategies not only foster a sense of responsibility and order but also strengthen a professional work culture oriented toward enhancing the quality of education.